Medicinal plant images - I.E, Cock (Pharmacognosy Communications)
The genus Xanthorrhoea (Australian grasstrees) is a small genus of slow growing and very long living plants which are endemic to Australia. The leaves of one species, Xanthorrhoea johnsonii, have recently been shown to display toxicity towards brine shrimp[9,10] and have an anaesthetic/sedative effect.[11] Recent studies have determined the phytochemical composition of X. johnsonii leaf extracts and identified o-hydroxycinnamic acid as the compound likely to be responsible for the sedative effect.[12] The same study postulated that this compound may produce its sedative effect by altering endogenous serotonin levels. Interestingly, the sedative effect has only been detected for leaves taken from plants during drought conditions. Leaf extracts from the same plants during times of high rainfall lack the sedative effect. It is therefore likely that whilst this compound may be constitutively expressed at low levels, its production is up-regulated during times of stress to function as a chemical deterrent to foraging animals and thus has a protective role in X. Johnsonii.